Financial Literacy and SME Sustainability in Chitwan and Nawalparasi: A Mediation Analysis - Pokharel, Sunil (BMC Journal of Scientific Research, 2025)
The Nepalese economy depends on small and medium enterprises (SMEs) which are not only the small and medium businesses but also fail within their first years of existence due to mismanagement of finances and lack of capital. This paper investigates the impact of financial literacy on the sustainability of SMEs in rural Nepal and in this regard, this study focusses to understand the mediating role that access to finance, and financial risk attitude play in the SMEs. This study employed the quantitative research method as well as explanatory research design and sampled 385 owners of SME in Chitwan and Nawalparasi districts in order to fill in the questionnaires having 42 items. The partial least squares structural equation modeling (PLS-SEM) was the analysis applied in the study to analyze the relationship between the variables. These findings suggest that the two dimensions of financial literacy have a significant direct and indirect effect on the success of business in making it easy to access finance and hence risk-taking attitudes. In particular, education, business experience, and digital literacy are very important antecedents of financial literacy. The paper concludes that the policy interventions must focus on the integrated financial and digital literacy education to create a robust SME sector.